2022
DOI: 10.1007/s10753-022-01698-x
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as a Potential Specimen to Monitor IL-6, TNF-α and IL-10 in COVID-19 Patients

Abstract: The SARS-CoV-2 instigated “cytokine storm” elicited upon infection is known to majorly cause lung injury and even mortality in severe cases. Early clinical prognosis to alleviate the exaggerated release of inflammatory cytokines is thus looked upon. Considering the recent attention and advantages of saliva as a clinical specimen, i.e. ease and painlessness of collection, which does not require trained staff and could allow self-sampling, the present study attempts to explore saliva for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…IL-6, TNF-α, and IL-1β, saliva levels were determined by using ultrasensitive ELISA immunoassays (R&D Systems, Minneapolis, MN, USA) according to the manufacturer's instructions [53][54][55]. The assays were based on a double-antibody sandwich technique.…”
Section: Quantification Of Inflammatory Markers Levels In Salivamentioning
confidence: 99%
“…IL-6, TNF-α, and IL-1β, saliva levels were determined by using ultrasensitive ELISA immunoassays (R&D Systems, Minneapolis, MN, USA) according to the manufacturer's instructions [53][54][55]. The assays were based on a double-antibody sandwich technique.…”
Section: Quantification Of Inflammatory Markers Levels In Salivamentioning
confidence: 99%
“…Similar to the Chang et al study, a recently published trial to evaluate the levels of inflammatory cytokines in saliva from COVID-19 patients has suggested a correlation between systemic levels of inflammatory cytokines. 5 The researchers performed real-time polymerase chain reaction and compared the cycle threshold values of the cytokines instead of measuring protein levels of the cytokines, and suggested that saliva could be an alternative specimen to blood for monitoring inflammation in COVID-19 patients. 5 Nasal mucosa samples could be obtained in a noninvasive procedure, and we speculate that nasal mucosa sampling would valuable for the diagnosis and monitoring of respiratory virus-mediated diseases.…”
Section: Letter To the Editor Regarding "Nasal Inflammatory Profile I...mentioning
confidence: 99%
“…5 The researchers performed real-time polymerase chain reaction and compared the cycle threshold values of the cytokines instead of measuring protein levels of the cytokines, and suggested that saliva could be an alternative specimen to blood for monitoring inflammation in COVID-19 patients. 5 Nasal mucosa samples could be obtained in a noninvasive procedure, and we speculate that nasal mucosa sampling would valuable for the diagnosis and monitoring of respiratory virus-mediated diseases. I believe trials such as this are useful and must be performed more frequently in the future.…”
Section: Letter To the Editor Regarding "Nasal Inflammatory Profile I...mentioning
confidence: 99%
“…Особого внимания заслуживает изучение особенностей цитокинового профиля в слюне, поскольку данные характеристики отражают не только местные, но и системные нарушения. Согласно данным литературы, концентрация цитокинов в сыворотке крови и слюнной жидкости является сопоставимой [18]. Особую актуальность представляет изучение местной цитокиновой регуляции межклеточных взаимодействий при пищевой аллергии.…”
Section: Introductionunclassified